Individuals with schizophrenia and relevant psychotic disorders: A clinical population with increased incidence for involuntary admission due to suicidal behavior - Kaikoushi, Katerina; Bella, Evanthia; Middleton, Nicos; Alevizopoulos, Giorgos; Chatzittofis, Andreas; Stylianou, Konstantinos; Karanikola, Maria (My University, 2019)
Objective: Investigation of socio-demographic and clinical characteristics of individuals involuntary admitted in the Psychiatric Hospital of Cyprus with suicidal behavior. Material and Method: A descriptive correlation study with cross-sectional comparisons was performed in a sample of 40 individuals (Sampling period 12/2016–02/2018). Data collection was conducted via individual interviews using a structured questionnaire, encompassing demographic and clinical characteristics, along with the PANSS, HAM-D, YMRS and HAM-A scales to assess the intensity of psychotic, depressive, manic and anxiety symptoms. Results: The majority of the sample were Greek-Cypriots, 32 males and 8 females, between 25–34 years. 26 of them had a positive history of substance use, while 20 of them were meeting criteria for dual diagnosis. The most frequent clinical diagnosis was schizophrenia (15%) and relevant psychotic disorders (65%). The most common symptom coexisting with suicidal behavior was substance abuse (50%), while 35% of sample reported no adherence to medication during the period before suicidal behavior. The most frequent methods of suicide attempt were fall from height (20%) and overdose (20%). Positive history of substance use was positively and strongly associated with suicidal behavior (x2, p<0.001, Cramer’s V=0.629), as well as the type of admission diagnosis (x2, p[removed]
Keywords: Demographic characteristics; Dual diagnosis; Psychotic disorder; Schizophrenia; Suicidal behavior; Suicidality